2014
DOI: 10.1371/journal.pone.0103009
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factor of Local Recurrence after Balloon-Occluded TACE with Miriplatin (MPT) in Hepatocellular Carcinoma

Abstract: BackgroundMiriplatin (MPT) is a novel platinum complex used in TACE that shows promise for the treatment of hepatocellular carcinoma (HCC). However, rapid washout has been reported in some cases. Therefore, various methods of administration with MPT have been attempted to increase its therapeutic efficacy. One hopeful method is balloon-occluded TACE (B-TACE), but the therapeutic efficacy of B-TACE with MPT has not been evaluated.AimTo investigate the treatment outcomes and factors involved in local recurrence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 20 publications
3
29
1
Order By: Relevance
“…This is possibly because the number of patients in our EPIR-C-TACE group who could be treated with superselective TACE might have been fewer than in previous reports. The local control rate after MPT-B-TACE in the present study (median time to local recurrence, 8.3 M) might be comparable with previous reports regarding C-TACE using MPT and EPIR [14,32], but the present data tended to be lower than in previous reports regarding MPT-B-TACE [28,33,34]. This might be possibly caused by patient and tumor characteristics.…”
Section: Discussionsupporting
confidence: 85%
“…This is possibly because the number of patients in our EPIR-C-TACE group who could be treated with superselective TACE might have been fewer than in previous reports. The local control rate after MPT-B-TACE in the present study (median time to local recurrence, 8.3 M) might be comparable with previous reports regarding C-TACE using MPT and EPIR [14,32], but the present data tended to be lower than in previous reports regarding MPT-B-TACE [28,33,34]. This might be possibly caused by patient and tumor characteristics.…”
Section: Discussionsupporting
confidence: 85%
“…Further, Ishikawa et al reported that occlusion of the hepatic artery caused hemodynamic changes, and injection under these changes induced more effective accumulation of iodized oil [8]. In the present case, compared with CTA without balloon occlusion, arteriogram and CTA with balloon occlusion showed slight arterial enhancement, and much stronger and broader enhancement of the surrounding area of the tumor.…”
Section: Discussionmentioning
confidence: 40%
“…Hypovascular HCC has a poor arterial blood supply, so it is difficult to control with conventional TACE (C-TACE) [4,6]. Balloon-occluded TACE (B-TACE), which induces the dense accumulation of iodized oil in HCC to prevent proximal migration and leakage of iodized oil by occlusion of the hepatic artery, is a promising method for improving the efficacy of C-TACE [7,8]. Here, we report a case in which good therapeutic control of a hypovascular tumor suspected as poorly differentiated HCC (pHCC) was achieved using B-TACE in addition to C-TACE.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that B-TACE with MPT achieved relatively good local control of HCC (local recurrence rate, 11.1% at 6 months and 26.2% at 12 months) [5] . The mechanism of improved local control can be explained by the presence of anastomotic vessels, viscosity of lipiodol emulsion, and difference in size between the peripheral vessels in normal parenchyma and the vessels feeding into the HCC.…”
Section: Discussionmentioning
confidence: 98%
“…We have previously reported that the Hounsfield unit value of a tumor obtained from conventional CT immediately after B-TACE with MPT is predictive of the recurrence risk [5] .…”
Section: Introductionmentioning
confidence: 99%